Seismic characteristics of hybrid cold-formed steel wall panels. (October 2020) - Usefi, Nima; Ronagh, Hamid
Abstract: The current standards for seismic design of cold-formed steel (CFS) structures are only limited to the lateral force-resisting systems which are not appropriate for mid-rise constructions due to their low shear resistance. Therefore, innovative hybrid CFS systems have recently been proposed and developed in response to the needs of CFS provisions as well as lightweight steel industry in mid-rise construction. This paper presents an experimental program on lateral cyclic behaviour of six full-scale hybrid wall panels with truss structural design and aims to investigate and characterize the seismic performance of this new CFS solution. The performance of the wall panels is compared in terms of seismic characteristics and response modification factor (R factor). A comprehensive comparison between lateral strength to weight ratio of the hybrid panels of this study and 87 previously tested CFS walls is also carried out to investigate the capability of using hybrid walls in modular lightweight steel buildings. The cyclic results demonstrate that the seismic performance of specimens with appropriate truss frame is satisfactory considering their shear strength, ductility and R factor values. The high strength to weight ratio of the hybrid walls of this study compared to the previously tested CFS panels also indicates the hybrid panels are well appropriate for modular lightweight buildings in seismic regions.